2017
DOI: 10.15408/ijee.v4i2.5977
|View full text |Cite
|
Sign up to set email alerts
|

Moral Values in Narrative Texts of English Textbooks for Senior High School Students Published by the Ministry of Education and Culture

Abstract: This study aimed to reveal the moral values in the narrative texts of English textbooks for senior high school students published by the Ministry of Education and Culture and also the English teachers’ and students’ responses at SMK Triguna Utama, South Tangerang City, related to the topic under investigation. This research used content analysis design. The data sources were the narrative texts in the English textbooks and teachers’ and students’ responses. The data were collected through documentation, interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Another study is about moral values that can be found in an English textbooks. The moral values usually occur in the narratiev text and are usually concered with the value of goodness, justice, and honesty [39]. From previous studies, researchers see that learning can be integrated with multicultural education, issues of sexism and gender, ethnicity, cultural comparison, and moral values [40].…”
Section: Integration Alternativementioning
confidence: 99%
“…Another study is about moral values that can be found in an English textbooks. The moral values usually occur in the narratiev text and are usually concered with the value of goodness, justice, and honesty [39]. From previous studies, researchers see that learning can be integrated with multicultural education, issues of sexism and gender, ethnicity, cultural comparison, and moral values [40].…”
Section: Integration Alternativementioning
confidence: 99%
“…As a crucial part of the learning sources, textbooks play a pivotal role in integrating character education into the learning process [13][14][15][16][17]. It contains passages, dialogues, exercises, tables, practices, and other activities to cover the pedagogy competence into which the character education values can be incorporated [17][18][19]. From this point of view, one of the eligibility criteria of textbooks is the integration of the character values into the textbooks' contents [12].…”
Section: Introductionmentioning
confidence: 99%
“…English textbooks have great potential for building characters because language learning can indirectly instill various consciousness through reading texts, pictures, dialogues, and sentences in the required exercises [13,20]. Thus, studies have been conducted to identify the character education values included in English textbooks used in English classrooms across Indonesia [18,[21][22][23][24][25][26][27][28][29]. While [21,[23][24][25]27] identified the inclusion of character education in junior high school textbooks, [18,26,28,29] chose to analyze the representation of character education in senior high school textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…In senior and junior school, the students have to learn different text types such as narrative, descriptive, exposition, analytical exposition, etc. A narrative text is one sort of the literary texts (Setiawan & Fahriany, 2017). This type of text tells a story or past event and entertains the readers.…”
Section: Introductionmentioning
confidence: 99%